1976
DOI: 10.2307/1540594
|View full text |Cite
|
Sign up to set email alerts
|

THE TAXONOMY, DEVELOPMENT AND BROODING BEHAVIOR OF THE ANEMONE,CRIBRINOPSIS FERNALDISP. NOV

Abstract: The Actiniidae is the largest and most diverse of the families of sea anemones (Anthozoa: Actiniaria). In addition to the morphological diversity within this family, there is considerable diversity in larval development. The Actiniidae are generally considered to be highly advanced anemones, although Hand ( 1966) has argued that this family should be considered primitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1
1

Year Published

1976
1976
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 6 publications
0
12
1
1
Order By: Relevance
“…Diese treten bei spfiten Gastrulae in Erscheinung, worauf die Embryonen erste Rotationsbewegungen ausffihren (Sch~fer, in Vorbereitung). )~hn-liches trifft offensichtlich ffir Cribrinopsis fernaldi zu (Siebert & Spaulding, 1976), w~ihrend bei anderen Actinaria bewegliche Blastulae beschrieben werden (Gemmill, 1920(Gemmill, , 1922Spaulding, 1974).…”
Section: Blastulaunclassified
“…Diese treten bei spfiten Gastrulae in Erscheinung, worauf die Embryonen erste Rotationsbewegungen ausffihren (Sch~fer, in Vorbereitung). )~hn-liches trifft offensichtlich ffir Cribrinopsis fernaldi zu (Siebert & Spaulding, 1976), w~ihrend bei anderen Actinaria bewegliche Blastulae beschrieben werden (Gemmill, 1920(Gemmill, , 1922Spaulding, 1974).…”
Section: Blastulaunclassified
“…The presence of this anemone has been recognized by local fishermen for a long time, but it has never been identified by a scientific name. In Toyama Bay, the similar-looking anemones were previously documented by Uchida & Soyama (2001) as the Northeastern Pacific species Cribrinopsis fernaldi Siebert and Spaulding, 1976, although the description did not include sufficient morphological evidence to support that identification. The pinkish specimens obtained from Toyama Bay in the present study seemingly resembled C. fernaldi, but the number and arrangement of tentacles of the specimens differed significantly from the original description of C. fernaldi by Siebert & Spaulding (1976).…”
Section: Introductionmentioning
confidence: 53%
“…In Toyama Bay, the similar-looking anemones were previously documented by Uchida & Soyama (2001) as the Northeastern Pacific species Cribrinopsis fernaldi Siebert and Spaulding, 1976, although the description did not include sufficient morphological evidence to support that identification. The pinkish specimens obtained from Toyama Bay in the present study seemingly resembled C. fernaldi, but the number and arrangement of tentacles of the specimens differed significantly from the original description of C. fernaldi by Siebert & Spaulding (1976). Further investigation of the specimens confirmed that the anemone truly belonged to the genus Cribrinopsis but it was distinct from any other described species in the genus.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…In polar regions, few examples of associations between sea anemones and crustaceans have been documented so far. The bestknown example occurs in the North Pacific and Alaska, where the large sea anemone species, Cribrinopsis fernaldi Siebert & Spaulding, 1976, is used as a defensive shelter by several species of hippolytid, thorid and pandalid shrimps (Butler, 1980;Stevens & Anderson, 2000).…”
Section: Introductionmentioning
confidence: 99%